Knowledge and attitudes about Ebola vaccine among the general population in Sierra Leone. Issue 15 (4th April 2016) - Huo, Xiang; Shi, Guoqing; Li, Xinxu; Lai, Xuehui; Deng, Liquan; Xu, Feng; Chen, Mingquan; Wei, Qiang; Samba, Thomas; Liang, Xiaofeng
Highlights: The knowledge and attitude about Ebola vaccine in Sierra Leone was presented. Over half (55.8%) of the participants were aware of Ebola vaccine. Most were willing to take free vaccination, while only 26.6% were willing to pay. Awareness of vaccine was associated with free vaccination uptake willingness. Family income was associated with charged vaccination uptake willingness. Abstract: Background: Clinical trials of Ebola vaccine are ongoing. Before it becomes commercially available, understanding the Ebola vaccine-related knowledge and attitude of the general population is imperative to developing an effective vaccine coverage strategy. Methods: We conducted a survey including 400 participants from general communities of the West Area Rural District, Sierra Leone. Knowledge and attitudes about Ebola vaccine were investigated, and the determinants of having knowledge and a positive attitude toward accepting vaccination were identified. Results: Over half (55.8%) of the participants were aware of Ebola vaccine. About 60% of the participants were willing to be study subjects if the Ebola vaccine clinical trial were conducted in their communities. Most of the participants (72.5%) were willing to take Ebola vaccination if it was free of charge. Given that the vaccination was not free, the proportion willing to pay a fee to take the vaccination declined dramatically to 26.6%. Using a forward step-wise logistic model, monthly salary was identified as the single determinant (OR for every 100, 000 Leones increase: 1.17, 95%CI: 1.04–1.31) for awareness of Ebola vaccine, which was identified as the determinant (OR: 1.88, 95%CI: 1.17–3.02) for free vaccination uptake willingness. The combination of monthly salary, monthly average income of family members and their interaction was found to be associated with charged vaccination uptake willingness. Discussion: Measures are still needed to promote the Ebola vaccine awareness and knowledge updating. Free or low-priced vaccine could increase the vaccination acceptability of the general community population significantly.